(untitled) (Revista INTEREDU11, 2021)
This article presents one of the central findings of the doctoral research: “Educational experiences of Afro-descendant black women: An intersectional study”, in which the epistemic racism evidenced in the educational experiences of six Afro-descendant black women with doctoral studies in Colombia is retaken. This racism is especially revealed in higher education spaces, through three forms: eurocentric thinking, which gives priority to european knowledge and distorts the epistemes produced from other non-westernized worldviews; invisibility in the curriculum, manifests itself when in the different spaces of formal education the epistemic elaborations different to the eurocentric parameters are not shown or unknown; academic marginalization is identified through the undervaluation of content, the undervaluation of racialized groups and the underrepresentation of afro-descendant black men and women in academic production spaces. As closing ideas, some of the restrictions that afro-descendant black women experience as a product of this epistemic racism are presented.